The best horror of the year. Volume eleven - Datlow, Ellen; Billson, Anne; Moore, Ralph Robert; Cluley, Ray; Smith, Michael Marshall; Olde Heuvelt, Thomas, 1983-; Hicks, Sam; Sutton, Peter (Fiction writer); Bailey, Dale; DeMeester, Kristi; Langan, John (John Paul) (Night Shade Books, 2019)
The Best Horror of the Year showcases the previous year's best offerings in horror short fiction. This edition includes award-winning and critically acclaimed authors Joe Hill, Siobhan Carroll, Laird Barron, Gemma Files, Adam-Troy Castro, and others. For more than three decades, award-winning editor and anthologist Ellen Datlow has had her finger on the pulse of the latest and most terifying in horror writing. Night Shade Books is proud to present the eleventh volume in this annual series, a new collection of stories to keep you up at night.